Biscarbocyanine dye for fluorescence imaging: Binding with albumin and DNA, cell accumulation, intracellular distribution and molecular modeling. (February 2023) - Kostyukov, Alexey A.; Mestergazi, Mikhail G.; Egorov, Anton E.; Shmykova, Аnna М.; Shibaeva, Anna V.; Markova, Alina A.; Podrugina, Tatyana A.; Pogonin, Vladimir I.; Radchenko, Eugene V.; Palyulin, Vladimir A.; Shtil, Alexander A.; Nekipelova, Tatiana D.; et al.
Abstract: The photophysical characteristics of a new bis-carbocyanine dye (BCD) with 4-methylpyridine fragment in the polymethine chain as well as its interaction with human serum albumin (HSA) and DNA were studied by means of steady-state and time-resolved optical absorption and fluorescence spectroscopies. We also obtained the rate of penetration and localization of BCD in the human colon adenocarcinoma cells (HTC116) and the data on its dark and photoinduced cytotoxicity toward these cells. The molecular dynamics method was employed to detect the localization of the BCD molecule within the HSA and DNA structures and to assess the BCD conformational behavior in different environments. The BCD binding constants to HSA and DNA were (8.2 ± 2.3) × 10 4 M −1 and (2.6 ± 1.3) × 10 5 M −1, respectively. The BCD fluorescence quantum yield increases 10-fold after binding to HSA. The molecular docking and molecular dynamics analysis showed that BCD bound to HSA is located in a wide moderately polar pocket between the IIA and IIIA albumin subdomains. BCD demonstrated rapid infiltration into the HCT116 cell interior and exceptionally low phototoxicity toward these cells which is explained by the absence of the BCD triplet state upon direct photoexcitation. This makes BCD a promising fluorescence agent for in vivo imaging in angiography. In the field of medical diagnostics, there is a request for the creation of fluorescent labels with fluorescence in the 650–700 nm range for existing equipment that does not require IR lasers and cameras. Highlights: The biscarbocyanine dye intensively absorb light at 670nm ( ε = 2.2 × 10 5 M −1 cm −1 )) and has high affinity to DNA and albumin. Dye fluorescence 10-fold increase after binding with albumin, molecular dynamics simulation indicates that molecule localized between binding sites IIA and IIIA. Dye effectively accumulates in cell, staining nuclei in 60 minutes, not causing apoptosis.